PERHITUNGAN TELUR TOXOCARA CATI DAN JUMLAH SEL DARAH PUTIH PADA KUCING LIAR (Felis catus) DI DUKUH KUPANG SURABAYA - bagus uda palgunadi; Roeswandono Roeswandono; Olan Rahayu Puji Astuti Mussa; Micco Joshua Apriano Pangaribuan (Fakultas Kedokteran Hewan Universitas Wijaya Kusuma Surabaya, 2019)
The research aimed to know the degree of infection from egg calculated and increased numbers of white blood cells (eosinophils and lymphocytes) in wild cats (Felis catus). The samples of the research as many as 30 wild cats around the Around of Dukuh Kupang Surabaya . The examination was done by Mc Master method with 100x magnification and the calculated of white blood cells (eosinophil and lymphocytes). The results showed the degree of toxocariasis infection in wild cats (Felis catus) in Surabaya in Dukuh Kupang was seen from the average value of the 468.3 egg examination and the calculated of white blood cells (eosinophilic and lymphocytes) with an average value of eosinophilic 0.73 x103/μl and lymphocytes 10.72 x103/μl. This study used descriptive method. Toxocariasis infection was included in the degree of moderate infection in wild cats (Felis catus) in Dukuh Kupang Surabaya with moderate degree.